2019
DOI: 10.4054/demres.2019.40.51
|View full text |Cite
|
Sign up to set email alerts
|

Parental leave policies and continued childbearing in Iceland, Norway, and Sweden

Abstract: BACKGROUND Demographic theories maintain that family policies that support gender equality may lead to higher fertility levels in postindustrial societies. This phenomenon is often exemplified by the situation in the Nordic countries. These countries have parental leave policies that promote a gender-equal work-care balance for both parents, and these countries have comparatively high fertility levels. However, very little is known about the association between these policies and childbearing at the individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 54 publications
0
39
0
Order By: Relevance
“…As to gender theories, there is an urgent need to expand the theory towards the male perspective (e.g., Jalovaara et al 2019). Despite the still existing gender inequalities in labour market outcomes, the trend towards the equalisation of care work at home may have unexpected fertility consequences (e.g., Duvander et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As to gender theories, there is an urgent need to expand the theory towards the male perspective (e.g., Jalovaara et al 2019). Despite the still existing gender inequalities in labour market outcomes, the trend towards the equalisation of care work at home may have unexpected fertility consequences (e.g., Duvander et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A recent register study from Iceland, Norway and Sweden showed a positive association between fathers' leave use and second births in all three countries (Duvander et al 2019). However, there was a negative association between fathers' parental leave use and third births in Norway and Sweden.…”
Section: Gender Theories In the Finnish Contextmentioning
confidence: 91%
“…When we look at parity distributions in the Nordic countries, we see that childlessness levels are around the European average (Sobotka 2017a), and that the two-child norm is strong (Frejka 2008;Duvander et al 2019). In all of the Nordic countries, ultimate childlessness rose slightly starting with the 1950s cohorts, but plateaued for the 1960-1970s cohorts at a level ranging from 12% in Norway to 15% in Sweden (Andersson 2009;Jalovaara et al 2019).…”
Section: [Figure 1 About Here]mentioning
confidence: 94%
“…Understanding fertility in the Nordic countries can contribute to our understanding of fertility trends in countries beyond the region, as the Nordic countries are often seen as forerunners in fertility behavior, and a number of recent fertility theories are based on the empirical associations between gender equality and fertility observed in the Nordic countries (Duvander et al 2019). It has, for example, been argued that at later phases in the demographic transition, improvements in gender equity may prevent fertility from falling to very low levels (Esping-Andersen 2009;McDonald 2000McDonald , 2013.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation